Analysis of 3D cracked components repaired by adhesively bonded patches using FEM-BIEM coupling. (August 2020) - Pham, Binh V.; Nguyen, Thai Binh; Rungamornrat, Jaroon; Limkatanyu, Suchart; Bui, Tinh Quoc
Highlights: FEM-BIEM coupling is implemented for analysis of 3D cracked components repaired by adhesively bonded patches. Patches and adhesive layers are tackled by the FEM whereas the cracked body is efficiently handled by the weakly singular BIEM. Special crack-tip elements are adopted to enhance the approximation of the near-front relative crack-face displacement. SIFs are extracted directly from the solved crack-front data on special crack-tip elements. Proposed technique yields highly accurate SIFs with use of relatively coarse meshes. Abstract: This research proposes an accurate computational procedure for the three-dimensional analysis of cracked components after being repaired by patches with the adhesive bonding. The technique was implemented based on the coupling between a finite element method (FEM) and a weakly singular, boundary integral equation method (BIEM). The FEM was utilized to tackle both the patches and adhesive layers, whereas the BIEM was employed to efficiently handle the elastic cracked medium. To enhance the approximation, an asymptotic structure of the near-tip field is properly integrated in the discretization of the jump in the crack-face displacement in the vicinity of the crack boundary. This, in addition, offered a direct means to post-process for the stress intensity factors (SIFs) in terms of the solved data along the crack front. Extensive results are then reported to demonstrate the accuracy and convergence of the implemented BIEM-FEM coupling and the effect of the relative stiffness of the patches and adhesive layers on the reduction of the SIFs along the crack front.